Angielsko-polski slownik skrotow : elektronika, informatyka, teleinformatyka - Bosakirski, Bogdan; Skrzynska, M. (Maria) (Warszawa : Wydawn Naukowo-Techniczne, 1992)
A dictionary of electronic and telecommunication terms and acronyms for Polish speakers.
Polish and English.
Keywords: Electronics -- Abbreviations -- Dictionaries; Electronics -- Abbreviations -- Dictionaries -- Polish; Computers -- Abbreviations -- Dictionaries; Computers -- Abbreviations -- Dictionaries -- Polish; Telecommunication -- Abbreviations -- Dictionaries; Telecommunication -- abbreviations -- Dictionaries -- Polish; English language -- Dictionaries -- Polish